Identification of the mummy that inspired Hergé’s character Rascar Capac - Ziemendorff, Stefan (2023)
This article puts an end to speculation about the source of inspiration of the Belgian cartoonist Hergé in the creation of his iconic character of Rascar Capac, the mummy of an Inca king in the comic “The Adventures of Tintin”. We review the hypotheses proposed in this respect by reviewing Hergé’s use of sources for the creation of his imagery, before comparing the iconography of the image of Rascar Capac with the images proposed as source of inspiration. The conclusion is that the character of Rascar Capac is inspired by a drawing in the French encyclopaedia Larousse, which represents a mummy from the Chachapoyas area in northern Peru. This mummy is on display at the Musée de l’Homme in Paris, so the idea that a mummy on display at the Cinquantenaire Museum in Brussels was the source of inspiration is ruled out.